Recombinant human oviductin regulates protein tyrosine phosphorylation and acrosome reaction. Issue 5 (November 2016) - Zhao, Yuewen; Yang, Xiaojing; Jia, Zongchao; Reid, Robert L; Leclerc, Pierre; Kan, Frederick W K
Abstract : The mammalian oviduct synthesizes and secretes a major glycoprotein known as oviductin (OVGP1), which has been shown to interact with gametes and early embryos. Here we report the use of recombinant DNA technology to produce, for the first time, the secretory form of human OVGP1 in HEK293 cells. HEK293 colonies stably expressing recombinant human OVGP1 (rHuOVGP1) were established by transfecting cells with an expression vector pCMV6-Entry constructed with OVGP1 cDNA. Large quantities of rHuOVGP1 were obtained from the stably transfected cells using the CELLSPIN cell cultivation system. A two-step purification system was carried out to yield rHuOVGP1 with a purity of >95%. Upon gel electrophoresis, purified rHuOVGP1 showed a single band corresponding to the 120–150 kDa size range of human OVGP1. Mass spectrometric analysis of the purified rHuOVGP1 revealed its identity as human oviductin. Immunofluorescence showed the binding of rHuOVGP1 to different regions of human sperm cell surfaces in various degrees of intensity. Prior treatment of sperm with 1% Triton X-100 altered the immunostaining pattern of rHuOVGP1 with an intense immunostaining over the equatorial segment and post-acrosomal region as well as along the length of the tail. Addition of rHuOVGP1 in the capacitating medium further enhanced tyrosine phosphorylation of sperm proteins in a time-dependent manner. After 4-h incubation in the presence of rHuOVGP1, the number of acrosome-reacted sperm induced by calcium ionophore significantly increased. The successful production of rHuOVGP1 can now facilitate the study of the role of human OVGP1 in fertilization and early embryo development.